Chronic Pepsin Exposure Increases Cell Proliferation and Promotes Tumor Growth of Hypopharyngeal Cells. (23rd August 2013) - Kelly, Elizabeth A.; Samuels, Tina L.; Johnston, Nikki
Abstract : Objectives: 1) Investigate the role of reflux, specifically pepsin, in laryngopharyngeal carcinogenesis. 2) Evaluate effects of chronic pepsin exposure on cell proliferation, apoptosis, and colony forming ability in hypopharyngeal cells. Methods: Human hypopharyngeal squamous cell carcinoma FaDu cells were chronically exposed to nonacidic porcine pepsin (exposed for 24 hours, 4 times over 2 weeks at the following concentrations: 0.01mg/ml, 0.1 mg/ml, and 1mg/ml). Precise wounds were created in confluent cell plates. Rates of cell invasion into wounds were quantified. Separately, cell viability of chronic pepsin exposed FaDu cells acutely treated with paclitaxel was measured. Finally, a clonogenic assay was performed on these cells to measure effects of chronic pepsin exposure on colony forming ability. Results: In the invasion assay, an increased rate of relative wound density was observed in pepsin treated (0.01mg/ml, 0.1mg/ml) cells compared to control ( P = 0.003, P < 0.001), suggesting greater rates of cell proliferation. Pepsin treated (0.1 mg/ml) cells had a greater cell viability compared to control after exposure to paclitaxel ( P < 0.03) demonstrating greater apoptosis resistance. Chronic pepsin exposure (0.1mg/ml, 1mg/ml) was associated with dose dependent increase in colony forming ability relative to control ( P < 0.001), supporting the role of pepsin as a tumor promoter. Conclusions: Hypopharyngeal cells chronically exposed to pepsin demonstrated an enhanced rate of cell proliferation and increased resistance to apoptosis and colony forming ability relative to control cells. These experiments indicate that chronic pepsin exposure acts as a tumor promoter in cellular transformation of airway epithelium, suggesting a role for pepsin in laryngopharyngeal carcinogenesis attributed to gastric reflux.